Faktor-faktor yang Mempengaruhi Kesiapan Perawat Anestesi Melakukan Tindakan General Anestesi di RSUP Mataram Nusa Tenggara Barat - Titiek Suharti; Yustiana Olfah; Abdul Majid (Journal of Health (JoH), 2016)
Background : The provision of the type of anesthesia in patients undergoing surgery can be performed under general anesthesia, and with the anesthetic to a specific body part (regional anesthesia). The type of anesthesia used in surgery, either by using general anesthesia or regional anesthesia with each having its own complications. Readiness of each participant looks diverse, there is no action in the first prepare medications and tools so often happens unpreparedness in implementing the action. Readiness of nurses in providing anesthesia is influenced by various factors such as age, education, work experience, knowledge and gender. Methods : The aim of research to explore preparedness for nurse anesthetists in general anesthetic action. This study used a naturalistic qualitative research. Participants in this study is a nurse anesthetist who is still on active duty in the department of West Nusa Tenggara Province. Intake of total participants performed the sampling technique. Data collection was conducted in natural conditions, the primary data sources and data collection techniques through observation, in-depth interviews to the participants to explore the role of a nurse anesthetist does and documentation. Data obtained through the data collection process immediately processed and analyzed by the researchers. Results of the study : The study states that the age of anesthesia nurses between 21 to 59 years, that the longer the period of employment will be more and more experience and better prepared for the patient, not the readiness of gender and all have the same roles and functions. Suggestion : Readiness nurse anesthesia before and during work is crucial to achieve satisfactory results in implementing the anesthesia.